A Bibliometric Analysis of Buzz Marketing : Research Areas, Concerns, and Suggestions for Advancement - Mahajan, Yogesh; Gadekar, Ashutosh (Indian Journal of Marketing, 2021)
Buzz marketing is widely used by marketers to generate buzz about products in the market. The purpose of this paper was to provide a complete overview of the existing ’buzz marketing’ literature and to study current trends and future directions for researchers interested in exploring and contributing to the field of buzz marketing. The bibliometric and network methods of analysis of citation and co-citation were used to achieve the purpose of this research paper. This research included an evaluation of articles published in the Scopus database journals from 2001 â€“ 2019. The bibliometric analysis was carried out using VOS Viewer software. The findings showed that the number of papers dedicated to the study of â€œbuzz marketingâ€ has diminished significantly in recent years, though there has been a significant increase in the number of activities to create buzz through buzz marketing by companies. In addition, the paper highlighted some of the area’s most prominent papers. A conceptual model of buzz marketing has been developed from this bibliometric analysis. Lastly, the paper emphasized the new trends and addressed the relevant challenges faced in buzz marketing. This study concentrated exclusively on buzz marketing concepts, trends and challenges, and future directions.